A post mortem study on the length of the human adrenal glands - Siddiqua, D; Ara, S; Nahar, N; Hena, H; Johora, F (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i1.13538 JAFMC Vol.8(1) 2012 pp.40-42